PERHITUNGAN SISTEM HIDROLIK UNTUK PENGGERAK PISAU PADA MESIN PENGHAPUS MARKA JALAN - Nanang Ali Sutisna; Muhammad Munajad (President University, 2020)
One of very important and vital tool in road marking is road mark erasing machines. In general, the machine used to repair road markings is a road marking erasing machine that is pushed manually. However, this machine has a disadvantage that requires a long time in the process of erasing the road marking, so making it less efficient. Therefore, the truck road mark erasing machine is one of the options to replace the erasing machine that is pushed manually. The machine uses a grinding system with a vertical blade eraser position and hydraulic power to drive the blades as it is able to withstand shock loads and thrust upwards due to the removal process, having overload protection, and the size of components are not large. The study started with doing observation to the existing manual erasing machine, then determining the required blades and calculating as well as selecting the required components of the hydraulic system. Based on the calculation, the blade specification was obtained and selected, i.e surface milling cutter of type WFX12200R from Sumitomo Electric Hardmetal Corporation having rotation speed 750 rpm, hydraulic motor from Danfoss of type OMR-80 having torque 136 Nm dan displacement 80.3 cc/rev., and using hydraulic pump from Parker of type 0210 having displacement 21 cc/rev. From the test result in the field, this machine is three times faster than the manually pushed machine, less number of the blade used, and the engine as a resource on the machine is more durable.